Implementation of an organizational infrastructure paediatric plan adapted to bronchiolitis epidemics. Issue 2 (February 2020) - Lavilledieu, David; Abassi, Hamouda; Mercier, Gregoire; Guiraud, Myriam; Chaffaut, Guillaume Du; Milesi, Christophe; Cambonie, Gilles; Gavotto, Arthur; Jeziorski, Eric; Amedro, Pascal
Abstract: Introduction: Acute bronchiolitis epidemics are known to destabilize healthcare structures and stand as a major public health issue. Our tertiary care regional university hospital designed an organizational infrastructure paediatric plan (OIPP) to adapt to bronchiolitis epidemics. This study aimed to assess the impact of the OIPP on the length of stay and quality of care of children hospitalized for bronchiolitis. Methods: This epidemiological study analyzed data from 2 epidemic seasons before and after the OIPP implementation. The OIPP used a standardized algorithm of patient orientation and a 4-level stratification of care. Results: A total of 1636 children were included in the study, with 718 children before and 918 children after the OIPP implementation. The length of stay significantly decreased after the OIPP implementation, from 5.1 ± 6.8 days to 3.9 ± 3 days ( P  < 0.001). The 30-day readmission for bronchiolitis remained stable (4.6% vs. 3.4%, P  = 0.2). The net annual patient service revenue increased from 1, 292, 532 € to 1, 545, 720 €. Conclusion: The implementation of the OIPP resulted in a significant decrease in the average hospital length of stay. This plan improved patients' quality of care while maintained a balanced budget. Trial registration number: ClinicalTrials.gov NCT03663660.